Astrocytic Ca2+ signaling is reduced during sleep and is involved in the regulation of slow wave sleep - Bojarskaite, Laura; Bjørnstad, Daniel M.; Pettersen, Klas H.; Cunen, Céline; Hermansen, Gudmund Horn; Åbjørsbråten, Knut Sindre; Chambers, Anna R.; Sprengel, Rolf; Vervaeke, Koen; Tang, Wannan; Enger, Rune; Nagelhus, Erlend A. (Nature Communications, 2020)
Astrocytic Ca2+ signaling has been intensively studied in health and disease but has not been quantified during natural sleep. Here, we employ an activity-based algorithm to assess astrocytic Ca2+ signals in the neocortex of awake and naturally sleeping mice while monitoring neuronal Ca2+ activity, brain rhythms and behavior. We show that astrocytic Ca2+ signals exhibit distinct features across the sleep-wake cycle and are reduced during sleep compared to wakefulness. Moreover, an increase in astrocytic Ca2+ signaling precedes transitions from slow wave sleep to wakefulness, with a peak upon awakening exceeding the levels during whisking and locomotion. Finally, genetic ablation of an important astrocytic Ca2+ signaling pathway impairs slow wave sleep and results in an increased number of microarousals, abnormal brain rhythms, and an increased frequency of slow wave sleep state transitions and sleep spindles. Our findings demonstrate an essential role for astrocytic Ca2+ signaling in regulating slow wave sleep.
Im Titel ist "2+" hochgestellt
Gesehen am 02.09.2020